PPLFS: A High Performance Consensus Method for Improving Throughput and Scalability in Blockchain Network - et. al., K. Lino Fathima Chinnarani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Blockchain has decentralized and immutable data structures, similar to traditional transaction systems. In the proposed PPLFS (Parallel Proof of Luck and Fair Share Model) framework, a scheme is designed to allow more than one miner to use the block of transactions, eventually increasing the throughput in terms of transactions per second. In the meantime, more than one leader could increase the availability and avoid network roadblock. This work leverages fair share technique and parallel mining technique to transform the blockchain into a multi-users operating system and multiple leaders could be permissible to promote their computing resources. This also reduces the transaction confirmation time for the stakeholders.